In vitro dissolution study of acetylsalicylic acid solid dispersions. Tunable drug release allowed by the choice of polymer matrix - Policianova, Olivia; Brus, Jiri; Hruby, Martin; Urbanova, Martina (Pharmaceutical development and technology, 2015)
Due to their high versatility and diverse excipient options, solid dispersions (SDs) are an elegant choice for the formulation of active pharmaceutical ingredients with inconvenient solubility. Four distinct types of polymers with different physicochemical properties [polyvinylpyrrolidone, poly[N-(2-hydroxypropyl)-metacrylamide], poly(2-ethyl-2-oxazoline), and polyethylene glycol] and variable molecular weights were compared to investigate the influence of the polymer matrix on drug release. To probe the extent of intercomponent interactions, acetylsalicylic acid (ASA) was used as a model active substance. Controlled drug release was demonstrated for all four types of polymer-ASA SDs created by the freeze-drying method. While the polyethylene glycol-ASA SD exhibited an increased dissolution rate, the other polymer-ASA systems exhibited significantly reduced drug dissolution kinetics compared to free ASA. Furthermore, in contrast to physical mixtures, the prepared SDs all exhibited zero-order dissolution kinetics for ASA. The dissolution rate was strongly dependent on the molecular weight of the polymer. These results demonstrate that the type of SD may be controlled by the chemical constitutions of the polymers and that appropriate selection of the molecular weight of the polymer matrix enables finely tuned drug release over a wide range of dissolution rates.
Keywords: controlled drug release; Acetylsalicylic acid; polymers; solid dispersions